Using mid-level cadres as substitutes for internationally mobile health professionals in Africa. A desk review - Dovlo Delanyo (BMC, 2004)
Abstract Background Substitute health workers are cadres who take on some of the functions and roles normally reserved for internationally recognized health professionals such as doctors, pharmacists and nurses but who usually receive shorter pre-service training and possess lower qualifications. Methods A desk review is conducted on the education, regulation, scopes of practice, specialization, nomenclature, retention and cost-effectiveness of substitute health workers in terms of their utilization in countries such as Tanzania, Malawi, Mozambique, Zambia, Ghana etc., using curricula, evaluations and key-informant questionnaires. Results The cost-effectiveness of using substitutes and their relative retention within countries and in rural communities underlies their advantages to African health systems. Some studies comparing clinical officers and doctors show minimal differences in outcomes to patients. Specialized substitutes provide services in disciplines such as surgery, ophthalmology, orthopedics, radiology, dermatology, anesthesiology and dentistry, demonstrating a general bias of use for clinical services. Conclusions The findings raise interest in expanding the use of substitute cadres, as the demands of expanding access to services such as antiretroviral treatment requires substantial human resources capacity. Understanding the roles and conditions under which such cadres best function, and managing the skepticism and professional turf protection that restricts their potential, will assist in effective utilization of substitutes.